2007
DOI: 10.1016/j.bone.2006.11.030
|View full text |Cite
|
Sign up to set email alerts
|

Sustained phosphorylation of mutated FGFR3 is a crucial feature of genetic dwarfism and induces apoptosis in the ATDC5 chondrogenic cell line via PLCγ-activated STAT1

Abstract: The most frequent type of rhizomelic dwarfism, achondroplasia (ACH), is caused by mutations in the fibroblast growth factor receptor 3 (FGFR3) gene. Mutations in FGFR3 result in skeletal dysplasias of variable severity, including mild phenotypic effects in hypochondroplasia (HCH), severe phenotypic effects in thanatophoric dysplasia types I (TDI) and II (TDII), and severe but survivable phenotypic effects in severe achondroplasia with developmental delay and acanthosis nigricans (SADDAN). To explore the molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 42 publications
3
20
0
Order By: Relevance
“…As determined by densitometry, the activation of STAT1 by wild-type FGFR3 in HeLa cells was ∼5.5-fold lower than in K650M (Fig. 2), similar to Harada et al [10] or Su et al [5], who found the wild-type FGFR3 activating STAT1 to the levels 4.8-fold or 20-fold lower than K650M.…”
Section: Resultssupporting
confidence: 85%
“…As determined by densitometry, the activation of STAT1 by wild-type FGFR3 in HeLa cells was ∼5.5-fold lower than in K650M (Fig. 2), similar to Harada et al [10] or Su et al [5], who found the wild-type FGFR3 activating STAT1 to the levels 4.8-fold or 20-fold lower than K650M.…”
Section: Resultssupporting
confidence: 85%
“…Several lines of evidence supported that PLCγ is widely distributed, activated by receptor or non-receptor tyrosine kinases, and involved in cell proliferation, differentiation, apoptosis, and metastasis of mammal cells, including chondrocytes [4,5,6,8]. For example, Harada et al [8] reported that PLCγ mediated FGFR3-induced STAT1 activation and this signaling cascade involved in the induction of apoptosis in the chondrogenic cell line ATDC5.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Harada et al [8] reported that PLCγ mediated FGFR3-induced STAT1 activation and this signaling cascade involved in the induction of apoptosis in the chondrogenic cell line ATDC5. Here, we demonstrated that PLCγ1 was expressed in normal articular and OA chondrocytes, and PLCγ1 was highly expressed in OA chondrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Increased apoptosis was found in the cartilage of mice overexpressing FGF2 [38], however other studies failed to confirm this effect [39, 40] (P. Krejci and W. R. Wilcox, unpublished). Ectopic expression of activating FGFR3 mutants induces apoptosis in ATDC5 chondrogenic cells and RCS chondrocytes [41] (Figs 5, S2), however this effect may represent an artifact of FGFR3 overexpression rather then a true physiological response.…”
Section: Discussionmentioning
confidence: 99%